Investigation of Dynamic Thiol Disulfide Homeostasis in Young Cattle With Pneumonia - ERTAŞ , Fatma; KIZILTEPE, Şemistan; MERHAN, Oğuz (MAS Journal of Applied Sciences, 2023)
The aim of this study was to investigate blood levels of thiol and disulfide, a new oxidative stress marker of oxidant and antioxidant balance, or thiol/disulfide ratios in cattle diagnosed with pneumonia and to determine its usefulness as a new prognostic inflammatory marker. The animal material of the study consisted of 20 cattle diagnosed with pneumonia as a result of clinical examinations, aged between 01-02 years, male and female were not important. Total thiol, native thiol, disulfide levels and dynamic thiol disulfide balance were measured chlorometrically with a spectrophotometer. As a result, no significant difference was found between pre-treatment and post-treatment levels. (p<0.05). It is thought that an oxidative stress occurs in diseased animals according to the values measured before and after treatment. It is also anticipated that the application of a real treatment for the causative agent will reduce the oxidative stress.